Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Di Rumah Sakit Jiwa Grhasia Selama Pandemi COVID-19: Factors Affecting Employee Performance at Grhasia Mental Hospital During the Covid-19 Pandemic - Worowulan, Santi Hapsari; Mudayana, Ahmad Ahid (Universitas Ahmad Dahlan, 2022)
Background: The Covid-19 pandemic has caused the hospital workload to increase which causes employees who work in hospitals to experience stress because they are always required to always provide the best service under any conditions. Based on this, efforts are needed in order to improve employee performance by using factors that affect employee performance. This study aims to determine the effect of work motivation, work environment, and organizational culture on employee performance at the Grhasia Mental Hospital during the Covid-19 pandemic. Methods: This research is quantitative research with a cross sectional approach. The population of this study were employees with the status of State Civil Apparatus who worked in the Grhasia Mental Hospital with 84 research samples that met the inclusion and exclusion criteria. Results: Based on the results of the Correlation Pearson test, it shows that there is a relationship between work motivation, work environment, and organizational culture on employee performance at the Grhasia Mental Hospital during the Covid-19 Pandemic with a p-value of 0.000 (p < 0.05). Conclusion: There is a relationship between work motivation, work environment, and organizational culture on employee performance at the Grhasia Mental Hospital during the Covid-19 Pandemic. For this reason, hospitals need to maintain motivation, work environment and organizational culture properly so that the performance of employees is maximized.